The Effect Of The Kahoot-Assisted Discovery Learning Model On The Mathematical Critical Thinking Ability - Hatimah, Husnul; Syahrul Azmi; Eka Kurniawan (Sigma&Mu: Journal of Mathematics Education, Mathematics, Statistics and Data Science, 2026)
The purpose of this study is to ascertain how the Discovery Learning learning paradigm, with Kahoot's assistance, affects the mathematical critical thinking abilities of SMAN 1 Utan class X pupils throughout the 2024/2025 academic year. This type of research is a quasi-experimental with a Post-test Only Control Group Design, involving two classes, namely the experimental class (X-6) and the control class (X-5). While the control class employs a traditional learning model, the experimental class uses the Discovery Learning learning paradigm with Kahoot's help. Post-test questions on critical thinking abilities and observation sheets for learning implementation serve as the research tools. According to the findings, the experimental class's average post-test score was 78.27, which was higher than the control class's average score of 64.89. A statistically significant difference between the two classes was revealed by the Mann-Whitney U test. With an effectiveness of 78.93%, the effect size (Cohen's d) of 0.80407 suggests a moderate effect. The experimental class is primarily in the very high category on the interpretation and evaluation indicators, while the control class is primarily in the high category on the analysis indicator and low on the inference indicator, according to the distribution of critical thinking ability categories by indicator. These results indicate that the use of Kahoot-assisted Discovery Learning can influence students' critical thinking abilities overall.